Produksi Kue Brownies sebagai Upaya Meningkatkan Nilai Ekonomi Singkong di Krajan Blimbing Dolopo Madiun - Muzakki, Hawwin (Amalee: Indonesian Journal of Community Research and Engagement, 2020)
Cassava, one of the staple foods of Indonesian people beside rice and sago, is promoted by the government as rice consumption replacements, together with corn, sago or potatoes. Cassava is indeed very easy to plant in all types of land, as in Krajan Hamlet, Blimbing Village, Dolopo District, Madiun Regency where almost every house has cassava plants on its garden. This fact encourages the engagement team to take the initiative to provide training of creative cassava processing. This activity aims to increase the economical value of cassava, which is one of the assets in the Krajan Hamlet, and is expected to be able to increase the family income, most of which are former migrant workers. Through the ABCD (Asset Based Community Development) method with some of its tools, found that the innovative and creative cassava process training in the form of "Si Engkong" cake can provide new insights and knowledge about cassava processing that have high selling points within the community. With a better processing of cassava, "Si Engkong" cake is expected to become a new trade commodity for the residents of Krajan Hamlet and its surroundings, so that it can raise the community's economy level. Keywords: ABCD, cassava processing, economical value, processed cassava, training Abstrak Singkong, salah satu makanan pokok masyarakat Indonesia selain nasi dan sagu, dipromosikan oleh pemerintah sebagai pengganti konsumsi beras, bersama dengan jagung, sagu atau kentang. Singkong memang sangat mudah ditanam di semua jenis tanah, seperti di Dusun Krajan, Desa Blimbing, Kecamatan Dolopo, Kabupaten Madiun di mana hampir setiap rumah memiliki tanaman singkong di kebunnya. Fakta ini mendorong tim pengabdi untuk mengambil inisiatif memberikan pelatihan pengolahan singkong. Kegiatan ini bertujuan untuk meningkatkan nilai ekonomis singkong, yang merupakan salah satu aset di Dusun Krajan, dan diharapkan mampu meningkatkan pendapatan keluarga, yang sebagian besar adalah mantan pekerja migran. Melalui metode ABCD (Pengembangan Masyarakat Berbasis Aset) dengan beberapa alatnya, ditemukan bahwa pelatihan proses singkong yang inovatif dan kreatif dalam bentuk kue "Si Engkong" dapat memberikan wawasan dan pengetahuan baru tentang pemrosesan singkong yang memiliki nilai jual tinggi. Dengan pengolahan singkong yang lebih baik, kue "Si Engkong" diharapkan menjadi komoditas perdagangan baru bagi penduduk Dusun Krajan dan sekitarnya, sehingga dapat meningkatkan tingkat ekonomi masyarakat. Kata Kunci: ABCD, nilai ekonomi, olahan singkong, pengolahan singkong, pelatihan